The financial planning journey: a grounded theory towards bias mitigation - Jugnandan, Shreeya (College of Accounting, 2024)
Behavioural finance suggests that individuals behave in a less than optimal manner. The decision-making of investors is subject to behavioural biases, which represent systematic deviations from logic and rationality. Research at the intersection of behavioural finance and financial planning has the potential to significantly improve the welfare of individuals through enhanced decision-making. This thesis explores the potential that financial advice may have toward debiasing investors. Debiasing investors has the potential to positively influence investor welfare and improving individuals' financial decisions has the potential to extend its positive effects on a broader scale. For instance, the South African government remains concerned about the growing number of individuals who rely on the state for financial support due to insufficient retirement assets. Improving individuals' decision-making could result in better savings and investment decisions for the individual. This research draws on behavioural finance concepts to systematically develop new theory. This research uses a constructivist, grounded theory approach. In-depth interviews were undertaken with 12 qualified financial planners in South Africa (of whom two formed part of a pilot study). Financial planners have the capacity to detect bias and deviations from logic within their clients. Financial planners seek to correct these deviations from logic through a two-phase approach entailing both pervasive and tailored techniques for their clients' scenarios. Ultimately, the efficacy of debiasing techniques must be contextualised within the broader financial planning process. The substantive grounded theory this research explicates discusses the debiasing process that individuals might undergo when they seek financial advice. The grounded theory produced by this research, “The Theory of the Financial Planning Journey”, articulates how the relationship between the investor and the financial advisor, underpinned by trust, functions to create an environment that is conducive to debiasing. The process of building and establishing a relationship during the financial planning journey enables the financial advisor to deploy techniques to help mitigate threats, such as biases, to the journey. The more partial a client is to the advisor, the greater the efficacy of the debiasing techniques the advisor may use (such as education or probing questions). This theory contextualises debiasing strategies as a toolkit of techniques to be implemented by the financial advisor. The use of each strategy changes depending on the bias and type of client presented. Although research about behavioural biases and debiasing methods is well documented within finance literature, this research represents a unique academic contribution in multiple ways. First, it approaches a behavioural finance problem with a qualitative, constructivist methodology that is uncommon within the research paradigm. Second, it extends the literature about financial planners by providing a novel, theoretical contribution regarding the role that planners might play in supporting bias mitigation of their clients. There are limited endeavours in behavioural finance literature that systematically seek to develop new theory. Debiasing literature is largely focused on testing debiasing strategies in isolation. This grounded theory suggests how multiple debiasing techniques may work within the process of financial advice. Third, this research identifies specific policy recommendations to improve investor welfare in the future. From a practical perspective, The Theory of the Financial Planning Journey has the propensity to influence the practice of financial advice. This research highlights the importance of relationship-building between advisor and client. Recommendations to policymakers therefore include elevating the importance of social skills when considering what core competencies are required for an individual to qualify as a certified financial planner.